Diversity of ants in Adams, Ilocos Norte, Philippines - Alejos, Mary Shan Faye; Carullo, Denise; Valdez, Jacelle (2014)
Ants are among the most diverse, abundant and ecologically significant organisms and in the Philippines, they are very diverse. However, Philippine ant fauna is very poorly explored and records are few. This study was conducted to determine the diversity of ants in Adams, Ilocos Norte. Two sites in a secondary forest of Adams were selected wherein twig breaking (TB), pitfall trap (PT), leaf litter technique (LL) and opportunistic Sampling (OS) were used to collect ants. A total of 1296 ants belonging to 23 genera were collected and classified to four subfamilies namely Myrmicinae, being the most diverse, followed by Formicinae, Ponerinae and Dolichoderinae. Myrmicinae is known to include the most diverse and dominant species of ants worldwide. Twenty-five percent of genera known in the Philippines including Carebara and Euprenolepis, only recorded in Negros, were found in Adams, Ilocos Norte. This is by far the most extensive and first record of ant diversity in the Ilocos Region which is then extends our knowledge on the geographical distribution of the ants across the country. Crematogaster was found to be the most abundant among the genera followed by Pheidologeton and Pheidole. Of the techniques used, TB was the most efficient, suggesting that twigs are common nesting habitat for ants. Tetramorium was captured by all of the methods used and may indicate that it have a wide range of habitat prefeence. Results indicate abundance of ant vary across genera, with more species and more abundant ants inhabiting twigs. There is a secondary forest. Further studies should be conducted in nearby more intact forest habitats to determine the extent of diversity in the whole area -- Author's abstract.